2006
DOI: 10.1002/cncr.22013
|View full text |Cite
|
Sign up to set email alerts
|

Excess risk of subsequent primary cancers among colorectal carcinoma survivors, 1975–2001

Abstract: METHODS. Using 1975Using -2001 data from the Surveillance, Epidemiology, and End Results (SEER) Program, we assembled 262,600 index cases of colorectal carcinoma to assess the occurrence of subsequent primary cancers in 13 noncolonic sites. Observed (O) subsequent cancers were compared with those expected (E) based on age-/sex-/race-/year-/site-specific rates in the SEER population. The standardized incidence ratio (SIR) and the absolute excess risk (AER) represent 'O 7 E' and 'O -E,' respectively. RESULTS.Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 70 publications
8
27
1
3
Order By: Relevance
“…In this study, colorectal cancer and stomach cancer showed the highest incidences of occurrence as second primary cancers, and this finding is consistent with previous studies (Table 4) [13][14][15][16][17][18]. It is conceivable that the high occurrence of gastric cancer in Korean colorectal cancer patients is merely a reflection of the high incidence of gastric cancer in Korea.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, colorectal cancer and stomach cancer showed the highest incidences of occurrence as second primary cancers, and this finding is consistent with previous studies (Table 4) [13][14][15][16][17][18]. It is conceivable that the high occurrence of gastric cancer in Korean colorectal cancer patients is merely a reflection of the high incidence of gastric cancer in Korea.…”
Section: Discussionsupporting
confidence: 92%
“…Each MPC was analyzed as if it was the first multiple primary with no regard for any intervening cancer diagnoses and associated treatment. Other studies have used a similar approach [7,9,11].…”
Section: Discussionmentioning
confidence: 99%
“…[3] One of the challenges faced by the growing number of survivors is the possibility of being diagnosed with a subsequent tumor, [4] with its associated implications in terms of poorer quality of life [5] and decreased long-term survival. [6] Several Australian and international studies in recent years have examined the risk of developing new primary cancers following an initial CRC diagnosis [7][8][9][10][11][12]. The focus of most of these studies has been on identifying which cancer types were more likely to occur after the initial CRC, with inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…21 Cress et al use 1992-2001 SEER data to examine temporal changes in CRC incidence, 22 whereas Ahmed et al use 1975Ahmed et al use -2001 SEER data to examine the excess risk of noncolonic primary cancers among CRC survivors. 59 Parikh-Patel et al utilize data from the California Cancer Registry to examine stage at diagnosis with respect to urban/rural residence. 60 Finally, Coughlin et al describe eight intervention projects funded by CDC's Division of Cancer Prevention and Control intended to promote CRC screening among diverse populations.…”
Section: Overview Of Chaptersmentioning
confidence: 99%